Integration of Augmented Reality in Temporal Bone and Skull Base Surgeries - Taku Ito; Taro Fujikawa; Takamori Takeda; Yoshimaru Mizoguchi; Kouta Okubo; Shinya Onogi; Yoshikazu Nakajima; Takeshi Tsutsumi (Sensors)
Augmented reality technologies provide transformative solutions in various surgical fields. Our research focuses on the use of an advanced augmented reality system that projects 3D holographic images directly into surgical footage, potentially improving the surgeon’s orientation to the surgical field and lowering the cognitive load. We created a novel system that combines exoscopic surgical footage from the “ORBEYE” and displays both the surgical field and 3D holograms on a single screen. This setup enables surgeons to use the system without using head-mounted displays, instead viewing the integrated images on a 3D monitor. Thirteen surgeons and surgical assistants completed tasks with 2D and 3D graphical surgical guides. The NASA Task Load Index was used to assess mental, physical, and temporal demands. The use of 3D graphical surgical guides significantly improved performance metrics in cochlear implant surgeries by lowering mental, physical, temporal, and frustration levels. However, for Bonebridge implantation, the 2D graphical surgical guide performed better overall (p = 0.045). Participants found the augmented reality system’s video latency to be imperceptible, measuring 0.13 ± 0.01 s. This advanced augmented reality system significantly improves the efficiency and precision of cochlear implant surgeries by lowering cognitive load and improving spatial orientation.